2006
DOI: 10.1177/089686080602600109
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Intraperitoneal Interleukin-6 System during the First Year of Peritoneal Dialysis

Abstract: Objective To investigate if intraperitoneal and systemic interleukin-6 (IL-6) and soluble IL-6 receptor (sIL-6R) are related to each other and to peritoneal solute transport rate (PSTR). Design Longitudinal study in retrospectively selected patients. Setting Peritoneal dialysis (PD) unit of a university-based hospital. Patients and Methods 31 PD patients on treatment with conventional glucose-based solutions participated in a longitudinal study. IL-6 and sIL-6R were measured in plasma and overnight effluent, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
74
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 28 publications
11
74
4
Order By: Relevance
“…When conventional high-glucose PD solutions were used, the peritoneal transport characteristics seemed to be changed as early as one year, and the correlation between dialysate IL-6 and peritoneal small solute transport was lost. 10 In our study, however, although the patients' population included shortand long-term PD patients, the positive association of dialysate IL-6 with the peritoneal solute transport and peritoneal protein leakage was demonstrated. Furthermore, the interquartile range).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…When conventional high-glucose PD solutions were used, the peritoneal transport characteristics seemed to be changed as early as one year, and the correlation between dialysate IL-6 and peritoneal small solute transport was lost. 10 In our study, however, although the patients' population included shortand long-term PD patients, the positive association of dialysate IL-6 with the peritoneal solute transport and peritoneal protein leakage was demonstrated. Furthermore, the interquartile range).…”
Section: Discussioncontrasting
confidence: 53%
“…8,19 However, recent well-controlled prospective studies have shown that intra-peritoneal IL-6, but not systemic IL-6 was associated with peritoneal solute transport in the early phase of PD, 3,10 while this association between dialysate IL-6 and small solute transport tended to be lost over time. 10 This time-dependent change was considered due to the functional or morphological change to the peritoneal membrane during the course of PD, and this change in the peritoneal membrane characteristics might have depended upon such factors as age, race, original kidney disease, complications, IL-6 genetic polymorphism 7,20 and biocompatibility of the PD solutions. 14,21 The cumulative exposure to a bioincompatible PD solution would induce a persistent intraperitoneal inflammatory response and might affect the peritoneal permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 It was previously described that intraperitoneal inflammation, as evaluated by dialysate levels of cytokines [particularly interleukin-6 (IL-6)] is associated with systemic inflammation and protein leakage through the peritoneum. 9 Interestingly, while dialysate IL-6 is associated with membrane functional changes, the relationship between systemic IL-6 and patient survival (similarly to other biomarkers of inflammation, such as CRP and serum albumin) has been consistent throughout published studies. 6,10 The increased levels of intraperitoneal markers of inflammation have been described during peritonitis episodes and remained elevated several weeks after the end of the antibiotic therapy, 10 suggesting that peritonitis may contribute to the chronic inflammatory state of the peritoneum.…”
Section: Discussionmentioning
confidence: 61%
“…It is likely that the predominant type of inherent fast transport status is dependent on population differences in the severity of inflammation. This is supported by the mean serum CRP concentration that was three times higher in the PD population from Sweden (22) compared to the population from the Netherlands (25).…”
Section: Inherent Fast Transportersmentioning
confidence: 70%